2017
DOI: 10.18203/2349-2902.isj20173104
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal tuberculosis: a clinicopathologic study in Kashmir valley

Abstract: Background: Tuberculosis is a major health hazard in India. Because of its diverse manifestations, difficult diagnosis, widespread complications, prolonged morbidity and increased mortality the study of this disease becomes even more important. The objectives of the study were to study age and sex distribution of abdominal tuberculosis, to study association of abdominal tuberculosis with pulmonary tuberculosis, to study various clinical presentations of abdominal tuberculosis, to study various modalities for d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 3 publications
1
2
0
Order By: Relevance
“…However, some studies have reported pallor as the most common sign. 5,13,15 Bowel adhesion was the most common intraoperative finding seen in 84% cases in our series, other studies have also shown bowel adhesion as the most common intra-operative finding. 15,17 Adhesiolysis was the most commonly performed single surgical procedure in 28% cases.…”
Section: 14supporting
confidence: 62%
See 2 more Smart Citations
“…However, some studies have reported pallor as the most common sign. 5,13,15 Bowel adhesion was the most common intraoperative finding seen in 84% cases in our series, other studies have also shown bowel adhesion as the most common intra-operative finding. 15,17 Adhesiolysis was the most commonly performed single surgical procedure in 28% cases.…”
Section: 14supporting
confidence: 62%
“…15 Awasthi S and Chalya PL observed that 22.6% and 29% respectively were associated with pulmonary tuberculosis. 10,12 Abdominal pain was the most common symptoms seen in 86% cases.…”
Section: 14mentioning
confidence: 97%
See 1 more Smart Citation